A STUDY OF HEXAGONAL AND CUBIC ICE AT LOW TEMPERATURES - Kumai, Motoi (1967)
The formation of hexagonal and cubic forms of ice was studied by the use of a cold stage in an electron microscope within the temperature range of - 190 to 170 degrees C. Ice crystal specimens were made on cold substrates, i.e., a collodion film, gold foil, or copper grid on the specimen holder of the cold stage. The structural forms of the ice were detected with the electron microscope using the selected area electron diffraction method. The hexagonal form of ice formed on the cold substrates at temperatures from -90 to -100 deg C. At -100 to -130 deg C, both hexagonal and cubic forms of ice were detected. From - 130 to -160 deg C only cubic ice was found. At temperatures below -170 deg C, minute crystals of cubic ice were detected. No transformation of the structural form of ice from hexagonal to cubic or from cubic to hexagonal occurred when the temperature of the specimens was varied in the range of -90 to -160 deg C. The minute crystals of cubic ice formed below -160 deg C were transformed into larger cubic ice crystals by heating them to a temperature between -130 and -150 deg C. The lattice constants of hexagonal and cubic ice, and the coefficient of thermal expansion of ice were calculated from the experimental results.